Enoch - the Modern Apocalyptic Hero. Contemporary Cultural Representations of the Biblical/Apocryphal Patriarch - Szönyi, György E. (IKON, 2015)
Abstract Enoch is an evasive character from the Bible (Genesis 5, 18-19; Jude 14-15; Hebrews 11,5). More is known about his mission for the rebel angels who sinned with the daughters of men and his subsequent elevation to heaven from the apocryphal Books of Enoch, the third version of which also informs us that for his righteousness the patriarch was promoted to become the mighty angel, Metatron. These books were written in Hebrew/Aramaic and Greek during the first few centuries, then they fell into oblivion, however, from the time of the Renaissance, scholars and mystical enthusiasts were looking for them in vain. It wasn’t until 1773 when the Scottish explorer of Africa, James Bruce managed to bring copies of the Book of Enoch (written in the Ethiopic language) to Europe and thus a new career of the patriarch started in the Western cultural sphere which is vigorously developing still today. My survey will start with William Blake’s famous and shocking drawings of Enoch and the promiscuous angels, but soon I will turn to postmodern interpretations of Enoch. I will talk about three theoretical works, one of radical-feminist and environmentalist theology by Margaret Barker, the other by a radical Afro-American evangelical, Khamit Kush, the third one by two freemasons, who in their Uriel’s Machine proposed to present Enoch as the original founder of their order. These are interesting and challenging scholarly, or pseudo-scholarly appropriations of Enoch, but I plan to go even further in my conclusion by looking at two contemporary novels (Philip Pullman’s His Dark Materials, 2005) and Alton Gansky’s Enoch, 2008) and a postmodern cult film (Kevin Smith’s Dogma) in which Enoch-Metatron features as an important character, angel, or concept. Wherever possible, I use visual illustrations and parallels and intend to concentrate on the iconological aspects of the mentioned cultural representations. Abstract Henok je problematičan biblijski lik (Postanak 5, 18-19; Juda 14-15; Hebrejima 11,5). Više podataka pružaju sadržaji vezani uz njegovu misiju prema pobunjenim anđelima, koji su zgriješili s kćerima čovječjim, i njegovo kasnije uznesenje na Nebo, iz apokrifnih spisa Knjiga proroka Henoka. Treća verzija apokrifa kaže kako je patrijarh zbog svoje pravednosti postao moćan anđeo, Metatron. Djela su napisana na hebrejskom, aramejskom i grčkom jeziku u prvih nekoliko stoljeća, nakon čega su pala u zaborav - iako su od renesanse učenjaci i mistici uzalud tragali za njima. Tek je 1773. škotski istraživač Afrike, James Bruce, uspio u Europu donijeti primjerak Knjige proroka Henoka (napisane na etiopskom jeziku), čime je započela nova patrijarhova ‘karijera’ u zapadnoj kulturnoj sferi, koja se snažno razvija do danas. Autor započinje istraživanje poznatim i šokantnim crtežima Henoka i promiskuitetnih anđela Williama Blakea, nakon čega se nadovezuje na postmodernističke interpretacije Henoka. Tekst govori o tri teoretska djela: o djelu Margaret Barker, koje se bavi teologijom radikalnog feminizma i environmentalizma, o djelu Khamida Kusha, radikalnog afroameričkog evangelista, te o djelu Urielov stroj, dvojice masona, koji predlažu Henoka kao izvornog osnivača njihova Reda. Tekstovi predstavljaju zanimljive znanstvene ili pseudoznanstvene aproprijacije Henoka. U svome radu autor proširuje istraživačko područje promatrajući dva suvremena romana (Njegove tamne tvari, 2005., Philipa Pullmanna, te Enok, 2008., Altona Ganskyja) i postmodernistički kultni film (Dogma Kevina Smitha), u kojima se Henok-Metatron predstavlja kao važan lik, anđeo ili ideja. U tekstu se koriste vizualni prilozi i analogije te se raspravlja o ikonološkim aspektima spomenutih kulturoloških prikaza.